Whistleblowing and Group Affiliation: The Role of Group Cohesion and the Locus of the Wrongdoer in Reporting Decisions - Bergemann, Patrick; Aven, Brandy (Organization Science, 2023)
Conventional accounts describe whistleblowing as prosocial behavior, where whistleblowers are largely driven by a desire to help or improve their organization. Yet individuals are not only members of their organization; they also belong to internal social groups that affect behavior and influence decision making. In this paper, we focus on these intraorganizational dynamics and theorize two ways in which group affiliations are likely to affect whistleblowing. When an individual observes wrongdoing committed by a person affiliated with the same group, higher group cohesion decreases the likelihood of blowing the whistle because of potential whistleblowers’ greater loyalties toward group members and a desire to protect the reputation of the group. When an individual observes wrongdoing committed by a person not affiliated with the same group, higher group cohesion increases the likelihood of blowing the whistle, as potential whistleblowers feel they have the support of fellow group members, lessening fears of retaliation. Using unique data on actual and hypothetical whistleblowing among U.S. federal employees in 24 departments and agencies coupled with a vignette experiment, we find support for our arguments. By showing how group affiliations inform whistleblowing decisions, we reveal how variation in social structure leads to heterogeneity in responses to wrongdoing. Together, these results reveal tradeoffs in the detection of misconduct and help explain why wrongdoing in organizations may be so difficult to eradicate.